Entrepreneurship Sebagai Panggung Sosial Disabilitas Tunarungu dalam Berekspresi - Muhammad Iqbal Putra Bakti; Ario Gleetus; Hendy Defriyanto (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Appearance is an important aspect of social life, as appearance is seen as a form of self-expression. An individual must have the desire to show their best appearance to other individuals. But behind all that, not all individuals have the same self-confidence. Disabled people have physical limitations, they are shy to show who they are, afraid to appear in public spaces, and lack confidence. Mental development is stunted because they are closed off to other individuals who do not have anything in common with them. This situation can be overcome by means of entrepreneurship, where the role of entrepreneurship is a place for disabilities to establish relationships of interaction with the wider community. The daily adaptation and interaction between disabilities and the community provides a form of courage in presenting themselves on the social stage. The purpose of this study is to find out how a person with a disability gives his appearance to the public, as well as provide information on the influence of entrepreneurship on their struggle to achieve self-confidence. This research uses a qualitative method, ethnographic approach. The results of this study found that entrepreneurship provides a positive approach for people with disabilities in presenting themselves on the social stage. Entrepreneurship becomes a means of empowerment that can increase the confidence and mentality of disabilities, so that society can take from this solution to provide support to disabilities.